P10-T Correlation of various EEG patterns with multimodal prognostic factors in patients with post-anoxic coma. Issue 7 (July 2019) - Xhani, Rubjona; Beretta, Simone; Coppo, Anna; Bianchi, Elisa; Zanchi, Clara; Carone, Davide; Stabile, Andrea; Padovano, Giada; Sulmina, Endrit; Grassi, Alice; Bogliun, Graziella; Foti, Giuseppe; et al.
Abstract : Bilateral absence of N20, elevated NSE levels and anoxic brain injury signs in neuroimaging, are noted as predictors of poor outcome in comatose patients after cardiac arrest (CA). We evaluated the association of various EEG patterns with these prognostic factors in comatose patients post AC. In our study, 166 patients with cardiac arrest in coma were stratified according to 4 independent EEG patterns: benign, RSE, generalized periodic discharges [GPDs], malignant non-epileptiform. NSE level > 68 ng/mL, bilateral absence of median nerve SEP and moderate to severe anoxic brain injury on neuroimaging, were considered indicators of poor prognosis. Of 166 patients that were included, a benign EEG pattern was recorded in 76 patients (45.8%); RSE occurred in 36 patients, a periodic pattern (GPDs) was seen in 13 patients (7.8%); and a malignant non epileptiform EEG pattern was recorded in 41 patients (24.7%). The four EEG patterns were highly associated with different prognostic indicators. Patients with benign EEG pattern and RSE showed lower NSE levels and were less likely to show bilateral absence N20 responses and severe anoxic brain injury on neuroimaging. On the other side, patients with GPDs and malignant pattern were associated more frequently with bilateral absence of N20 responses, higher NSE levels and severe anoxic brain injury on neuroimaging. These data show that the a benign EEG pattern and RSE without periodisms, may be a predictor of a good outcome and a more aggressive treatment may be indicated in this patients, given the possibility of a better prognosis.